Dividual Turn: A Comparative Study of the Worldviews of the Japanese and the Melanesian Folks - Naruhiko Mikado (Hasanuddin University, 2019)
This study has three aims: the first is to illuminate the transformation in the minds of the Japanese people after the catastrophic earthquake in 2011—namely, the collective movement to reappraise the worth of bonds and connections between/among people. The second is to show that the ongoing spiritual change has a number of similarities with the worldview of the Melanesian folk which Marilyn Strathern analysed with the concept of “dividual”. The third is to generalize diverse insights which the two cases suggest and thus to seek a fresh way to see people and those relations which bridge over them. The argument begins with a discussion to prove the point of the first aim, then the second, and, after referring to what is not dealt with for future research, concludes by demonstrating that of the third. The contribution which this study will make for interdisciplinary scholarship is that it attests a literary text and an anthropological study can be employed to derive a philosophical discourse.